Combination of Metformin, Sodium Oxamate and Doxorubicin Induces Apoptosis and Autophagy in Colorectal Cancer Cells via Downregulation HIF-1α - Coronel-Hernández, Jossimar; Salgado-García, Rebeca; Cantú-De León, David; Jacobo-Herrera, Nadia; Millan-Catalan, Oliver; Delgado-Waldo, Izamary; Campos-Parra, Alma D.; Rodríguez-Morales, Miguel; Delgado-Buenrostro, Norma L.; Pérez-Plasencia, Carlos (Frontiers in Oncology, 2021)
Colorectal cancer (CRC) is the third leading cause of cancer-related death worldwide in both sexes. Current therapies include surgery, chemotherapy, and targeted therapy; however, prolonged exposure to chemical agents induces toxicity in patients and drug resistance. So, we implemented a therapeutic strategy based on the combination of doxorubicin, metformin, and sodium oxamate called triple therapy (Tt). We found that Tt significantly reduced proliferation by inhibiting the mTOR/AKT pathway and promoted apoptosis and autophagy in CRC derived cells compared with doxorubicin. Several autophagy genes were assessed by western blot; ULK1, ATG4, and LC3 II were overexpressed by Tt. Interestingly, ULK1 was the only one autophagy-related protein gradually overexpressed during Tt administration. Thus, we assumed that there was a post-transcriptional mechanism mediating by microRNAs that regulate UKL1 expression during autophagy activation. Through bioinformatics approaches, we ascertained that ULK1 could be targeted by mir-26a, which is overexpressed in advanced stages of CRC. In vitro experiments revealed that overexpression of mir-26a decreased significantly ULK1, mRNA, and protein expression. Contrariwise, the Tt recovered ULK1 expression by mir-26a decrease. Due to triple therapy repressed mir-26a expression, we hypothesized this drug combination could be involved in mir-26a transcription regulation. Consequently, we analyzed the mir-26a promoter sequence and found two HIF-1α transcription factor recognition sites. We developed two different HIF-1α stabilization models. Both showed mir-26a overexpression and ULK1 reduction in hypoxic conditions. Immunoprecipitation experiments were performed and HIF-1α enrichment was observed in mir-26a promoter. Surprisingly, Tt diminished HIF-1α detection and restored ULK1 mRNA expression. These results reveal an important regulation mechanism controlled by the signaling that activates HIF-1α and that in turn regulates mir-26a transcription.